F1 [videorecording (Blu-Ray)] - Kosinski, Joseph, 1974-; Kruger, Ehren, 1972-; Pitt, Brad, 1963-; Idris, Damson; Condon, Kerry, 1983-; Menzies, Tobias, 1974-; Ashley, Simone; Kingsman, Liz; Niles, Sarah; Whigham, Shea, 1969-; Bardem, Javier, 1969-; Bodnia, Kim, 1965-; et al. (Warner Bros. Entertainment, 2025)
"Sonny Hayes was the most promising phenom in the 1990s in Formula 1 until an accident on the track. Thirty years later, his former teammate Ruben Cervantes convinces him to come back and drive alongside hotshot rookie Joshua Pearce for one last shot at being the best in the world. Sonny's past catches up with him, and he finds that the road to redemption is not something you can travel alone."--